Age-specific Predatory Potential and Functional Response of Heteroneda billardieri Crotch (Coleoptera: Coccinellidae), Against Mango Leafhopper, Idioscopus clypealis Lethierry (Hemiptera: Cicadellidae) - Apolinario, Jena Joy G.; Medina, Celia dR.; Velasco, Luis Rey I.; Pamiloza, Raol P. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
This study evaluated the predatory potential and functional responses of the different stages of the yellow netted lady beetle (YNLB), Heteroneda billardieri, against all nymphal instars of the mango leafhopper (MLH) in the laboratory. The 3rd instar larva and the female and male adults of YNLB were offered varying densities of MLH in vials, and the number of consumed MLH was recorded after 24 hours. The prey-consumption data were analyzed using logistic regression to estimate the age-specific functional response to MLH. Results showed that the 3rd instar H. billardieri has the highest predatory capability relative to the adult predators. At the highest prey density, 3rd instar larvae consumed 14.67 and 15.33 of the 2nd and 3rd instar MLH, respectively. It also has the highest attack rate and shortest handling time, with values of 0.089 and 0.71, respectively. All tested stages of H. billardieri exhibit a Type II functional response, characterized by a curvilinear increase in predation rates with increasing prey density. The results imply that the field releases using the 3rd instar H. billardieri can achieve the highest biological control efficiency. However, field studies should be conducted to verify these results.